2017
DOI: 10.1016/j.vetimm.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced neutrophil extracellular trap formation in canine neutrophils is dependent on histone H3 citrullination by peptidylarginine deiminase

Abstract: Neutrophils release neutrophil extracellular traps (NETs), which are extracellular chromatin decorated with histones and antimicrobial proteins. Although known for antimicrobial properties, overzealous production of NETs (NETosis) may lead to cytotoxicity and multiple organ failure in sepsis. Pathogen-induced NETosis has been extensively studied in mice but its importance in dogs remains largely unknown. This study sought to characterize in vitro NETosis induced by E.coli LPS, including assessing the role of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…Because of its activity, the presence of citrullinated proteins, principally histones, is considered as a marker of PAD4-mediated NETosis (Brinkmann et al, 2016 ; Li et al, 2017 ). In accordance to other reports, our results showed that citrullinated proteins were scarce in control and PMA-treated neutrophils (Neeli and Radic, 2013 ; Konig and Andrade, 2016 ; Muth et al, 2017 ); however, abundant citrullinated proteins were seen in neutrophils treated with A23187 and amoebas.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its activity, the presence of citrullinated proteins, principally histones, is considered as a marker of PAD4-mediated NETosis (Brinkmann et al, 2016 ; Li et al, 2017 ). In accordance to other reports, our results showed that citrullinated proteins were scarce in control and PMA-treated neutrophils (Neeli and Radic, 2013 ; Konig and Andrade, 2016 ; Muth et al, 2017 ); however, abundant citrullinated proteins were seen in neutrophils treated with A23187 and amoebas.…”
Section: Discussionmentioning
confidence: 99%
“…Histone citrullination, catalzyed by the enzyme, peptidylarginine deiminase 4 (PAD4), alters the electrostatic interactions between DNA and histones causing chromatin decondensation and release of cfDNA during NETosis [ 18 ]. We have recently shown that lipopolysaccharide-mediated NETosis in vitro requires histone H3 hypercitrullination by PAD in canine neutrophils [ 9 ]. The substantial number of citH3 positive cells identified in culture-positive samples suggests that a similar cellular process also occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To date, NETs have not been documented in dogs with bacterial sepsis. Isolated canine neutrophils have been shown to release NETs in response to E. coli lipopolysaccharide and the chemical, phorbol 12-myristate 13-acetate [ 8 , 9 ]. Several methods of plasma cfDNA quantification have been described in dogs with sepsis, neoplasia and immune-mediated haemolytic anemia [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ET formation was described for the first time in human neutrophils in 2004 (Brinkmann et al , ), but has since also been reported for several different phagocytic cells in mammal (e.g. dogs, rodents, horses) (Etulain et al , ; Li, Ng & Tablin, ; Vargas et al , ) and non‐mammal vertebrate species (e.g. crocodile, fish, chicken) (Palić et al , ; Kozlowski et al , ; Pieper et al , ; Wen et al , ), as well as for invertebrates such as the social amoeba Dictyostelium discoideum (Zhang et al , ) and the earthworm Eisenia andrei (Homa et al , ).…”
Section: Introductionmentioning
confidence: 99%